Financial Accounting Development Paths and Alignment to Management Accounting in the Italian Context - Trucco, Sara.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book presents empirical evidence on the convergence of financial and management accounting in the Italian context. The author provides an overview of the development paths of financial accounting including its evolution, role of non-financial, forward looking and voluntary disclosures, and internal determinants such as corporate governance and business culture. The author uses the premises of agency, signalling, legitimacy and institutional theories in understanding this evolution, and includes the perspective of professional associations and academics on the topic. Based on survey data, the reader is provided with valuable insights into the Italian accounting scene.
Introduction -- Financial Accounting: Development Paths -- Premises for the Convergence of Financial Accounting and Management Accounting -- Drivers of the Alignment of Financial Accounting to Management Accounting -- Financial Accounting and Alignment to Management Accounting in the Italian Context -- Discussion on the Alignment of Financial Accounting to Management Accounting in the Italian Context.
Keywords: Business; Accounting; Bookkeeping; Corporate governance; Finance; Business and Management; Accounting/Auditing.; Finance, general; Corporate Governance; Electronic books